Poverty Reduction Support Credits : Armenia Country Study - Hicks, Norman (Washington, DC: World Bank, 2017)
Armenia gained its independence from the Soviet Union in 1991 and inherited a traditional Soviet- style command economy. After a period of hyperinflation and economic contractions, progress on basic reforms led to greater macroeconomic stability. The reform effort strengthened after 2000, aided by return flows of investment from the diaspora. Recognized for its prudent fiscal management and improved business environment, Armenia received a Rehabilitation Credit (RC) from the World Bank in 1995 and a series of five Structural Adjustment Credits(SACs) from 1996-2003 to maintain stability, accelerate growth, and sustain reform. The PRSC program in Armenia centered on four main themes that supported Armenia's poverty- reduction objectives: i) consolidating macroeconomic discipline and strengthening governance;ii) sharpening competition and entrenching property rights; iii) mitigating social and environmental risks; and iv) modernizing the rural economy. The PRSC also identified good governance and reduction of corruption as essential to achieving pro-poor growth. Furthermore, reforms implemented under the PRSC were intended to make the social sectors more efficient, raise the quality of services, and increase access for the poor.